Agritourism in Montenegro – Empirical research in the function of strategic development - Melović, Marica (Hotel and Tourism Management, 2022)
The aim of this paper is to consider the strategic opportunities and importance of agritourism development in Montenegro, identifying key factors that may help agritourism to position itself as an integral part of both rural and overall tourism offer of Montenegro. The paper contains empirical research, which was conducted using a questionnaire on a stratified random sample, and the data were analyzed using statistical methods – factor analysis and descriptive statistics. The author came to the conclusion that in the development of agritourism, Montenegro has not yet taken the competitive position it should have, considering its huge potential for development of this form of tourism. Based on the obtained results, the factors that have a significant impact on the development of agritourism were identified, and a set of recommendations for current and potential holders of agritourism offer was created, in order to improve their tourism and marketing strategy.